Revitalisasi Kulit dengan Body Scrub Kulit Buah Naga Merah: Dampak Variasi Asam Stearat dan Perbandingan dengan Produk Komersial - Suena, Ni Made Dharma Shantini; Juanita, Rr. Asih; Wardani, I Gusti Agung Ayu Kusuma; Antari, Ni Putu Udayana (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
The red dragon fruit peel (Hylocereus lemairei (Hook.) Britton & Rose) is rich in antioxidants like vitamins C, E, and A, along with alkaloids, terpenoids, flavonoids, saponins, and tannins, which protect against free radical damage. Despite its benefits, the peel is underused. This study compares the formulation and physical quality of a body scrub made from red dragon fruit peel extract to commercial products. Stearic acid was added to enhance consistency and stability, and commercial products served as benchmarks due to their compliance with physical, microbiological, and chemical standards. Formulations with stearic acid at 5% (F1), 10% (F2), and 15% (F3) were tested for physical quality—organoleptic properties, homogeneity, pH, adhesion, and spreadability—over 63 days as an intermediate time points, at controlled room temperature. Data were analyzed using SPSS Statistics 20 with a 95% confidence level (α = 0.05). Results showed that all formulations maintained a consistent pH of 6 and homogeneity. The adhesion properties were consistent across all formulas, showing no significant difference (p = 0.815; p > 0.05). In contrast, the spreadability exhibited a statistically significant difference between formulas (p = 0.001; p < 0.05). Stability tests revealed no significant differences in physical quality over time, indicating that the formulations remained stable. The body scrub formulated with red dragon fruit peel extract demonstrated stability and quality comparable to commercially available product. This ensures that the active ingredients in the body scrub remain potent, enabling them to effectively deliver their antioxidant properties to the skin.